Media Massa dalam Komunikasi Ekonomi - Yuliani, Ni Made (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
Mass communication uses mass media as a tool in the process of information inflation. Media such as internet, radio, television, surakabar, and others sebgainya. Media for modern society is very important. The public's need for the presence of mass media has made many changes in various lines of life. The pattern is formed by the presence of mass media. Mass media are also able to determine the pattern of thinking and community decision making in life. This mass media presentation is of course positive or negative.Mass media gives a relatively rapid change in various sectors of human life. Until people gradually enter into new cultural patterns. Without the mass media can create a number of needs. The mass media also gives guidance to the public about the standard of living worthy of a modern human being. Society and the environment also assess the fulfillment of these standards, thanks to this picture is influenced from what is seen, heard, and read from the mass media.Economic growth, political development, cultural change, even health affected by the mass media. Until the emergence of imitation style of the masses. This is what makes the economy about the lifestyle trend of the community can easily develop. The value of persuasion in communication is capable of making changes to the individual or the social system as a result of acceptance or rejection of an innovation.Economic development is relatively short thanks to the mass media. This impact is thanks to the monopoly in the management, supply, and utilization of information. Businesspersons simply showcase business expectations that they want to spread to the audience. This also makes economic growth more rapidly. Economic development in the various business can easily advance rapidly thanks to the mass media.